2022
DOI: 10.3390/ijms23137053
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the PI3K/AKT Intracellular Signaling Pathway in the AntiCancer Activity of Hydroxytyrosol, a Polyphenol from Olea europaea, in Hematological Cells and Implication of HSP60 Levels in Its Anti-Inflammatory Activity

Abstract: Hydroxytyrosol (HT), the main representative of polyphenols of olive oil, has been described as one of the most powerful natural antioxidants, also showing anti-inflammatory, antimicrobial, cardioprotective and anticancer activity in different type of cancers, but has been little studied in hematological neoplasms. The objective of this work was to evaluate the anticancer potential of HT in acute human leukemia T cells (Jurkat and HL60) and the anti-inflammatory potential in murine macrophages (Raw264.7). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The main phenolic components of VOO are the secoiridoid derivatives of hydroxytyrosol (HTy) and tyrosol (Ty), with the hydroxytyrosol-containing phenolic components having the highest biological activities. They are the most effective in preventing chronic diseases due to their superior ability to reduce chronic inflammation and oxidative damage and their potent anti-proliferative activity [ 3 , 4 ]. In this sense, scientific evidence on the health benefits of HTy has led the European Food Safety Authority (EFSA) to approve a health claim that states “olive oil polyphenols contribute to the protection of blood lipids from oxidative stress”.…”
Section: Introductionmentioning
confidence: 99%
“…The main phenolic components of VOO are the secoiridoid derivatives of hydroxytyrosol (HTy) and tyrosol (Ty), with the hydroxytyrosol-containing phenolic components having the highest biological activities. They are the most effective in preventing chronic diseases due to their superior ability to reduce chronic inflammation and oxidative damage and their potent anti-proliferative activity [ 3 , 4 ]. In this sense, scientific evidence on the health benefits of HTy has led the European Food Safety Authority (EFSA) to approve a health claim that states “olive oil polyphenols contribute to the protection of blood lipids from oxidative stress”.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is known that CLL cells are vulnerable to sudden and continuous activation of the PI3K/AKT signaling pathway [40]. Additionally, it has been reported that hydroxytyrosol inhibits the PI3K signaling pathway in acute human leukemia T cells (Jurkat and HL60) [55]. Regarding the shortlisted GO-BPs, 3 out of 16 were also highlighted from our computational verification meta-analysis: regulation of apoptotic process (GO:0042981), innate immune response (GO:0045087)and DNA metabolic process (GO:0006259).…”
Section: Discussionmentioning
confidence: 99%
“…HT is the second major OLE structure phenol [ 37 ], where the degradation of OL leads to the majority of its production [ 43 ]. The antiproliferative, proapoptotic, and anti-inflammatory properties of HT were recently evidenced in human neuroblastoma cells (SH-SY5Y), acute human leukemia T-cells (Jurkat and HL60), and colorectal cancer cells (HCT116 and LoVo) [ 44 , 45 , 46 ]. In this study, HT led to 50% inhibition of GB cell proliferation in the lowest concentration among all investigated phenolics of OLE by arresting the cell cycle in the S and G2/M phases, demonstrating its robust preventive capacity against GB.…”
Section: Discussionmentioning
confidence: 99%